Uttrakhand lok sabha election results on expected lines - Nautiyal, Annapurna (Social Science in Perspective)
This election clearly exhibited that BJP$1 (Bs organizational structure, was far more efficient, better and well organized than congress party$1 (Bs organizational structure. The internal divisions, fights, revengeful attitudes, public spats and choice of candidates by one of the oldest party of the state were also responsible for its loss in all seats. Actually the internal divisions and lack of on acceptable leadership was the major cause of Congress fall from the grace. This allowed a landslide win for BJP and Modi in Uttarakhand. Under such conduction the grand old party certainly needs to introspect and check the internal divisions. Fighting and develop a good leadership not only in the state but nationally also. Rahul Gandhi$1 (Bs defeat from Amethi seat in Uttar Pradesh and wiping out of Congress from all five seats in Uttrakhand indicates it clearly. However some goes for BJP also because though presently Modi wave and Amit Shah$1 (Bs strategies have given BJP a spectacular and unimaginable margin of win, but to repeat the same performance would be difficult if the state government which has fifty seven seats fails to perform well and remain complacent and slack in fulfilling the promises made for the agenda of development of hill areas. It is high time that the state BJP starts working on its weak sectors and focuses on delivery of results. - Reproduceds
Keywords: Elections - Uttarakhand